ELECTORAL DYNAMICS AND POLITICAL LEADERSHIP: A CASE STUDY OF ANGGI ARANDO A NON-LOCAL LEGISLATIVE MEMBER WHO SUCCESSFULLY MAINTAINED ELECTABILITY IN DAPIL 2 DKI JAKARTA - Dedi Purwanto (Jurnal Media Akademik (JMA), 2025)
This research is motivated by the electoral dynamics in urban areas that are increasingly complex, especially in DKI Jakarta as a political and social center inhabited by heterogeneous and rational voters. In this context, the success of a non-local legislator in maintaining electability is an interesting phenomenon to study, as seen in the figure of Anggi Arando in the Jakarta Constituency (Dapil) 2. This study aims to analyze the factors that influence the electoral success, including the dynamics of urban voter behavior, the political leadership style applied, the form of functional representation that is built, and the communication strategies and social networks used in maintaining public support. The research method used is a qualitative approach with a case study design through in-depth interviews, field observations, and documentation studies to comprehensively explore the data. The results show that urban voters do not place the candidate's locality as the main determining factor. Anggi Arando's success is supported by a combination of transformational and instrumental leadership that is able to build public trust, as well as functional representation that is reflected through responsiveness, public service, and effectiveness in handling citizens' complaints. Political communication strategies that integrate digital media and face-to-face interaction increase symbolic proximity and political presence in society. In addition, social networks with community leaders, local communities, and volunteers are a significant force in strengthening the legitimacy of non-local candidates. The implications of this study confirm that in the context of modern urban politics, leadership quality, representation effectiveness, and adaptive communication are dominant factors in the success of non-local candidates, as well as providing a strategic model for political contestation in urban areas.